Intuition and wisdom in decision making - Rocha Neto, Ivan (2018)
Paper aims This article discusses the importance of intuition and wisdom for timely andsuccessful decision making and highlights the features of intuitive leaders. Originality As engineers reach higher hierarchical levels, technical knowledge must be balanced with intuition, a matter that is not addressed in their education. Research method It is a theoretical essay illustrated by an example. Main findings Information is always incomplete and imperfect, and thus intuition plays a key role on effective decision making Implications for theory and practice It sheds light on the importance of intuition in decision making, which is not discussed in Engineering courses curricula. It also presents the example of Lynaldo Cavalcanti de Albuquerque, former President of the Federal University of Paraiba (UFPb) and the National Council of Scientific and Technological Development (CNPq), who can be a role model of a effective decision maker, and a visionary and intuitive leader.